Advancements in the examination of the preparedness of parents of children undergoing liver transplantation - He, Ting; Tang, Li Hua; Sa'at, Siti Fatimah (IIUM Press, 2024)
Liver transplantation is a very efficient remedy for liver ailments in children, and with advancements in technology, the anticipated survival rate after the surgery has also increased. Nevertheless, as a result of insufficient medical resources and the implementation of the quick rehabilitation approach, children are often released from the hospital prior to achieving complete recovery, leaving parents to assume the role of primary carers. Release preparedness, including the patient's physical state, mental wellbeing, and community assistance, is a significant indicator of a patient's adjustment to life after release. An efficient evaluation of discharge readiness may promote a seamless transition to home, minimize problems, and limit the need for further treatment and readmission. The objective of this research was to offer a comprehensive overview of the present condition regarding the preparedness of parents of children who have had liver transplantation to establish a foundation for evaluating and implementing appropriate interventions.